Crepipatella dilatata (Lamarck, 1822) (Calyptraeidae): An example of reproductive variability among gastropods - Zelaya, Diego Gabriel (2012)
Reproductive characteristics of a species are often defined from a small number of individuals collected from a single location at one particular time. However, this study reveals that the South American gastropod Crepipatella dilatata (Lamarck, 1822) shows an unusually high level of intraspecific variability in some key reproductive characteristics: the number of egg capsules brooded per female, the size of the egg capsules, the number of eggs per capsule and the sizes and size distributions of the uncleaved eggs. Larger females were more fecund than smaller ones, not because they produced more egg capsules, but because they produced capsules of significantly larger size. Such variability was evident not only when considering different populations, but also within a single population sampled in different years, as well as among specimens collected during a single sampling event. Thus our data emphasize the importance of obtaining information from numerous specimens per locality as well as from specimens from different localities and in different years when describing the reproductive characteristics of any particular taxon.